Analisis Kondisi Lingkungan Sekolah dan Implikasinya terhadap Disiplin Belajar Siswa: Studi Kualitatif di MA Muhammadiyah Nangahure - Angela Marici Nona Tiara; Katharina Woli Namang; Leny Maria Nona Lehan; Claudia Syrila Cindy; Sitti Umama (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
This study aims to examine the school environment and its impact on student discipline at MA Muhammadiyah Nangahure. The method used was a qualitative descriptive approach. Data collection was conducted through observation, in-depth interviews, and documentation studies involving the principal, teachers, and students as sources of information. The results indicate that the physical school environment is generally adequate; however, several limitations remain, For example, classroom comfort and lighting influence students' concentration and discipline. Social relationships, particularly interactions between teachers and students, play a crucial role in determining students' discipline. In addition, the school culture emphasizing religious values and discipline serves as a strength in supporting students’ discipline, although the implementation of rules and sanctions has not been fully consistent. The study concludes that both physical and social school environments have direct implications for students’ learning discipline. Therefore, optimizing school environment management, improving facilities, and strengthening teachers’ roles in enforcing discipline are necessary to enhance students’ learning discipline.